Effects of the COVID-19 crisis on survey fieldwork: Experience and lessons from two major supplements to the U.S. Panel Study of Income Dynamics - Sastry, Narayan; McGonagle, Katherine; Fomby, Paula (Survey research methods, 2020)
Two major supplements to the Panel Study of Income Dynamics (PSID) were in the field during the COVID-19 outbreak in the United States: the 2019 waves of the PSID Child Development Supplement (CDS-19) and the PSID Transition into Adulthood Supplement (TAS-19). Both CDS-19 and TAS-19 abruptly terminated all face-to-face fieldwork and, for TAS-19, shifted interviewers from working in a centralized call center to working from their homes. Overall, COVID-19 had a net negative effect on response rates in CDS-19 and terminated all home visits that represented an important study component. For TAS-19, the overall effect of Covid-19 was uncertain, but negative. The costs were high of adapting to COVID-19 and providing paid time-off benefits to staff affected by the pandemic. Longitudinal surveys, such as CDS, TAS, and PSID, that span the pandemic will provide valuable information on its life course and intergenerational consequences, making ongoing data collection of vital importance.